Testimony of John A. McCone on Geneva Test Ban Negotiations (United States. Government Printing Office., 1959)
Testimony of John A. McCone (1902-1991), chair of the Atomic Energy Commission (AEC), on Geneva test ban negotiation, given in hearing before the Subcommittee on Disarmament of the Committee on Foreign Relations, United States Senate. McCone reports on his recent attendance at the Conference on the Discontinuance of Nuclear Weapon. The conference, composed of the Soviet Union, the United Kingdom, and the United States, opened on October 31, 1958 and ended in January 1962.
Keywords: McCone, John A. (John Alex), 1902-1991; U.S. Atomic Energy Commission; United States. Congress. House. Committee on Foreign Relations; Nuclear weapons--Testing; Disarmament; Conference on the Discontinuance of Nuclear Weapon Tests (1958-1962 : Geneva, Switzerland)